1978
DOI: 10.1071/sr9780291
|View full text |Cite
|
Sign up to set email alerts
|

Water absorption by swelling seeds. II. Surface condensation boundary condition

Abstract: The previously developed model of water absorption by a swelling seed has been applied to imbibition and germination of wheat seed with the limiting supply condition of purely water vapour transport both with and without the presence of a porous medium. Experimental imbibition and germination data show that with vapour transport, the rate of imbibition and germination of wheat decreases with increasing distance from the supply source and that competition for water vapour occurs between seed. This competition e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
1

Year Published

1985
1985
2007
2007

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 11 publications
0
4
0
1
Order By: Relevance
“…They did not specify the distance from the seed to the vapor‐supplying liquid. Collis‐George and Melville (1978) measured imbibition by wheat under purely vapor transport, and found that distance from the liquid surface was a factor in imbibition rates. If the distance between the liquid surface and the seed surface influences both imbibition rates and final moisture content of seed, then studies of vapor imbibition will give very different results, depending on the methods used.…”
mentioning
confidence: 99%
“…They did not specify the distance from the seed to the vapor‐supplying liquid. Collis‐George and Melville (1978) measured imbibition by wheat under purely vapor transport, and found that distance from the liquid surface was a factor in imbibition rates. If the distance between the liquid surface and the seed surface influences both imbibition rates and final moisture content of seed, then studies of vapor imbibition will give very different results, depending on the methods used.…”
mentioning
confidence: 99%
“…Few experiments have been conducted in which seeds have been intentionally germinated in vapour alone, although several reports exist where this has occurred while pursuing other goals. As mentioned earlier, Owen (1952) determined that wheat imbibed with vapour alone germinated in 48 h at 20°C, and Collis-George and Melville (1978) observed germination in vapour in 60–80 h. In addition, Etherington and Evans (1986) used sealed Petri dishes packed with soil to germinate various native seeds in contact with soil of different water contents. They found that a piece of fibreglass filter paper placed between the soil and a seed made it easier to observe the seed, and caused no noticeable delay in germination.…”
Section: Can Vapour Really Be Sufficient?mentioning
confidence: 99%
“…Bruckler (1983) used a 1- to 6-mm air gap, and concluded that full imbibition of maize took three times longer in vapour than in liquid. Collis-George and Melville (1978) compared distances of 1 and 3 cm and measured 60 and 80 h for wheat germination to be completed. And, finally, Schneider and Renault (1997) placed maize grains 2 cm above water and concluded that it took ten times longer for them to imbibe in the presence of vapour than in liquid water.…”
Section: Behaviour Of Water Vapour In Soilmentioning
confidence: 99%
See 1 more Smart Citation
“…WEST, 1985), soluções com várias quantidades de produtos quimicos(POWELL & MATTHEWS, 1978; WOODSTOCK & TAO, 1981) e sistema de vapor expondo as sementes às diferentes condições de umidade relativa do ar(COLLIS-GEORGE & MELVILLE, 1978). Em todos os casos, a embebição pode ser realizada de maneira gradual e, para isso, basta controlar a quantidade de água disponível à semente(VERTUCCI,1989).Quando a embebição for realizada em substrato úmido, a água permanece retida no substrato pelo potencial mátrico e não há possibilidade de confundir os efeitos dos tratamentos com os efeitos devido a absorção de produtos químicos.…”
unclassified